2010
DOI: 10.1007/s12072-010-9184-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of gastroesophageal reflux disease in patients with chronic hepatitis B virus infection

Abstract: Background Although chronic liver disease is associated with gastroesophageal reflux disease (GERD), the impact of chronic hepatitis B virus (HBV) infection on this association remains unclear. We thus aimed to evaluate the relationship between chronic HBV infection and GERD.Methods In this prospective population-based study, 1,001 adult subjects who underwent an upper gastrointestinal endoscopic examination in a health check-up and completed a gastroesophageal reflux questionnaire were consecutively enrolled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Fatty liver was found to be associated with a higher prevalence of EE in a report from South Korea, but the study did not exclude the potentially confounding effects of excessive alcohol consumption, hepatitis B and hepatitis C [10]. Excessive alcohol consumption, hepatitis B and hepatitis C may play a role in fatty liver, and excessive alcohol consumption and hepatitis B may be related to the risk of EE [6,[11][12][13][14]. We thus excluded the subjects with hepatitis B, hepatitis C and excessive alcohol consumption in the current study, and the results showed that NAFLD was associated with increased risk of EE.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Fatty liver was found to be associated with a higher prevalence of EE in a report from South Korea, but the study did not exclude the potentially confounding effects of excessive alcohol consumption, hepatitis B and hepatitis C [10]. Excessive alcohol consumption, hepatitis B and hepatitis C may play a role in fatty liver, and excessive alcohol consumption and hepatitis B may be related to the risk of EE [6,[11][12][13][14]. We thus excluded the subjects with hepatitis B, hepatitis C and excessive alcohol consumption in the current study, and the results showed that NAFLD was associated with increased risk of EE.…”
Section: Discussionmentioning
confidence: 91%
“…and fatty liver [10,11]. Hepatitis B and hepatitis C may also play a role in fatty liver [12,13], while hepatitis B has been associated with EE [14]. Nonalcoholic fatty liver disease (NAFLD) is defined as a subgroup of fatty liver, which is not due to excessive alcohol consumption or other causes of steatosis [15,16].…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…After excluding patients who received proton pump inhibitors, histamine-2 receptor antagonists, aspirin, or NSAIDs in the 6 months preceding the invitation, or had a history of any gastrointestinal surgery, liver cirrhosis, or malignancy, 2752 participants were consecutively invited to enter this study and received screening, and 2604 responded to the survey on GERD and IBS [16]. A GERD patient was defined as any individual who has a diagnosis of endoscopic LA grade ≥ A or identified by RDQ score of at least 3.…”
Section: Study Populationmentioning
confidence: 99%
“…The RDQ is an instrument for the diagnosis of GERD that can be easily administered by primary care physicians in community settings and has been validated previously in Chinese populations [16,21]. It examines symptoms of heartburn, acid regurgitation, and dyspepsia, addressed using 12 questions on the frequency, severity, and duration of burning and pain behind the breastbone, acidic taste in the mouth, movement of materials upward from the stomach, and burning and pain in the upper stomach [22].…”
Section: Questionnaire and Medical Informationmentioning
confidence: 99%